2013
DOI: 10.1021/jp400646n
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis on the Optoelectronic Properties of Single Crystals of Thiophene-furan-phenylene Co-Oligomers: Efficient Photoluminescence due to Molecular Bending

Abstract: We theoretically analyze the optoelectronic properties of single crystals of 2,5-bis(4-biphenylyl) bithiophene (BP2T) and 2-(4-biphenyl)-5-[5-(4-biphenyl)-2-thienyl] furan (BPFT) molecules, aiming to provide a guiding principle for the material design of organic light-emitting transistors. The X-ray structure analysis and the density functional theory (DFT) calculations indicate that half of the BPFT molecules bend the π-conjugation plane in the crystal. The Marcus theory parametrized by the DFT calculations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Here, the exciton coupling includes contributions from both long-range Coulomb (Förster) and electron exchange (Dexter) mechanisms. When excited states were not involved in the electronic coupling between the pair (bacterio)chlorophylls, charge transfer integrals were calculated based on (bacterio)chlorophyll monomer orbitals and the Fock matrix of (bacterio)chlorophyll dimer ( 60 ). The calculation scheme for the electronic coupling ( 28 ) is implemented in the modified version of the GAMESS program.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the exciton coupling includes contributions from both long-range Coulomb (Förster) and electron exchange (Dexter) mechanisms. When excited states were not involved in the electronic coupling between the pair (bacterio)chlorophylls, charge transfer integrals were calculated based on (bacterio)chlorophyll monomer orbitals and the Fock matrix of (bacterio)chlorophyll dimer ( 60 ). The calculation scheme for the electronic coupling ( 28 ) is implemented in the modified version of the GAMESS program.…”
Section: Methodsmentioning
confidence: 99%
“…These maybe exploited in applications like OLEDs [ 17 ] or security features. Similar structure/optoelectronic property relationships in terms of absorption and PL were also probed using P3HT [ 96 99 ], water soluble P3HT [ 100 ], other thiophene based block copolymers [ 101 ], co-oligomers [ 102 ], or even systems like donor-acceptor semicrystalline polymers [ 103 ], and alternating co-polymers with fluorine and thiophene moieties [ 104 ]. For example, by means of temperature-dependent absorption and PL spectroscopy, it was shown that the optical emission is dominated in regioregular P3HT by weakly coupled H-aggregates (characterized by the inter-chain coupling of polymer chains) while the relative absorbance of the 0–0 and 0–1 vibronic peaks can be used to extract the intermolecular coupling energy in thin P3HT films cast from various solvents [ 96 ].…”
Section: Influence Of Molecular Conformations and Long-range Arrangemmentioning
confidence: 99%
“…Optical properties are determined by the behavior of the exciton. In general, the exciton of well-formed crystal has a high degree of freedom and has excellent optical properties [21,22]. The assembly of molecules to hexagonal crystals with well-defined morphologies requires driving forces from the molecules themselves, including molecular stacking and Van der Waals forces [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%